One approach is that we learn together, regardless of the language, regardless of the school subject: the translanguaging stance of teachers in a migration school scenario in southern Brazil - Anamaria Welp; Eduardo Sampaio; Gláucia Helena Sarmento Malta (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada)
ABSTRACT This article presents the results of a study conducted at Escola das Pontes, a school in southern Brazil that serves local, immigrant, and refugee students, primarily from Haiti and Venezuela. The research is grounded in the theory of translanguaging, which offers a humanizing approach that places students and their diverse repertoires at the center of learning, breaking down traditional language barriers. Through a critical-collaborative research perspective, the study investigated the educators’ translanguaging stance, i. e., their orientation towards social justice, across different subject areas during a teacher development meeting. The meeting aimed to create a space for educators to discuss their daily experiences and challenges in school. The results suggest most teachers demonstrate a translanguaging stance in their teaching, as they report using students’ language repertoires to leverage language and content learning. This is observed even before their formal introduction to translanguaging theory. Their approach values students’ ways of knowing and promotes linguistic diversity in favor of meaningful education. The teachers’ accounts reveal that learning in their classrooms is not hierarchical, as teachers and students learn together.